Controllable one-pot synthesis of a nest-like Bi2WO6/BiVO4 composite with enhanced photocatalytic antifouling performance under visible light irradiation. Issue 11 (5th February 2016) - Ju, Peng; Wang, Yi; Sun, Yan; Zhang, Dun
Abstract : Novel visible-light-sensitive Bi2 WO6 /BiVO4 nest-like hierarchical microspheres were controllably synthesized for photocatalytic antifouling. Abstract : In this study, a novel visible-light-sensitive Bi2 WO6 /BiVO4 composite photocatalyst was controllably synthesized through a facile one-pot hydrothermal method. The Bi2 WO6 /BiVO4 composite exhibited a perfect nest-like hierarchical microsphere structure, which was constructed by the self-assembly of nanoplates with the assistance of polyvinylpyrrolidone (PVP). The growth mechanism of the Bi2 WO6 /BiVO4 composite and the effect of its structure on its photocatalytic performance was investigated and proposed. Experimental results showed that the Bi2 WO6 /BiVO4 composites displayed enhanced photocatalytic antifouling activities under visible light irradiation compared to pure Bi2 WO6 and BiVO4 . Bi2 WO6 /BiVO4 -1 exhibited the best photocatalytic antifouling performance, and almost all (99.99%) Pseudomonas aeruginosa ( P. aeruginosa ), Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ) bacteria were killed within 30 min. Moreover, the Bi2 WO6 /BiVO4 -1 composite exhibited excellent stability and reusability in the cycled experiments. The photocatalytic antifouling mechanism was proposed based on the active species trapping experiments, revealing that the photo-induced holes (h + ) and hydroxyl radicals (˙OH) could attack the cell wall and cytoplasmic membrane directly and lead to the death of bacteria. The obviously enhanced photocatalytic activity of the Bi2 WO6 /BiVO4 -1 composite could be mainly attributed to the formation of heterojunctions, accelerating the separation of photo-induced electrons and holes. Furthermore, the large BET surface area combined with the wide photoabsorption region further improved the photocatalytic performance of the Bi2 WO6 /BiVO4 -1 composite. This study provides a new strategy to develop novel composite photocatalysts with enhanced photocatalytic performance for marine antifouling and water purification.